2019
DOI: 10.2196/12672
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Helpline and Reversible Contraception: Lessons From a Controlled Before-and-After Study in Rural India

Abstract: Background Researchers and activists have expressed concerns over the lack of availability and nonuse of reversible, modern, contraceptive methods in India for decades. New attempts to increase access, availability, and acceptance of reversible contraceptives need to be developed, instead of relying solely on female sterilization. Mobile health (mHealth) initiatives may offer one way to serve underprivileged populations who face challenges in sexual and reproductive health (SRH) in countries such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…We identified several examples of interventions and programmes that detailed a novel theory of change, developed in tailored way for a specific intervention. One example of this was applied by Kulathinal and colleagues [ 49 ]. This intervention drew on a theory of change developed through desk-based research that identified three key issues in contraceptive uptake: a lack of information, gender bias, and unavailability or inaccessibility of contraceptives.…”
Section: Resultsmentioning
confidence: 99%
“…We identified several examples of interventions and programmes that detailed a novel theory of change, developed in tailored way for a specific intervention. One example of this was applied by Kulathinal and colleagues [ 49 ]. This intervention drew on a theory of change developed through desk-based research that identified three key issues in contraceptive uptake: a lack of information, gender bias, and unavailability or inaccessibility of contraceptives.…”
Section: Resultsmentioning
confidence: 99%
“…Taking advantage of the rapid increase in phone access, family planning programs in several countries have started to use call centers to increase access to quality sexual and reproductive health information (Antillon et al, 2022; Corker, 2010; Kulathinal et al, 2019). In Nigeria, DKT’s Honey&Banana call center provides confidential family planning information and counseling, free of charge.…”
Section: Discussionmentioning
confidence: 99%
“…Research on smoking cessation hotlines has consistently shown that offering incentives, such as free nicotine patches or gum, substantially increases call volumes to these quitlines (An, Schillo, Kavanaugh, Luxenberg, et al, 2006; An, Schillo, Kavanaugh, Lachter, et al, 2006; Anderson, Kirby, Tong, Kohatsu, & Zhu, 2018; Bauer, Carlin-Menter, Celestino, Hyland, & Cummings, 2006; Cummings et al, 2006; Hood-Medland et al, 2018; Momin et al, 2014; Tong et al, 2023; Vijayaraghavan et al, 2018). Although several organizations operate family planning call centers (Antillon, Webbe, & Husken, 2022; Corker, 2010; Kulathinal, Joseph, & Saavala, 2019; Yagnik et al, 2015), to the best of our knowledge, there are no studies that examine whether e-vouchers can be effective for increasing use of such family planning hotlines.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Kulathinal et al . [ 27 ] showed that the use of reversible contraceptive methods (18% increase in the intervention area versus 2% increase in the control area) increased using mobile application. The results of this study are consistent with the present research on general self-care.…”
Section: Discussionmentioning
confidence: 99%